Acacia auriculiformis–derived bimodal porous nanocarbons via self-activation for high-performance supercapacitors - Bhat, Vinay S.; Jayeoye, Titilope John; Rujiralai, Thitima; Sirimahachai, Uraiwan; Chong, Kwok Feng; Hegde, Gurumurthy (Frontiers Media S.A., 2021)
Carbon nanomaterials derived from Acacia auriculiformis pods as electrodes for the electrochemical double-layer capacitors were explored. Four pyrolysis temperatures were set (400, 600, 800, and 1,000°C) to understand the role of temperature in biomass pyrolysis via a possible “self-activation” mechanism for the synthesis of carbon materials. The carbon materials synthesized at 800°C (AAC800) were found to exhibit a well-organized hierarchical porous structure, quantified further from N2 adsorption/desorption isotherms with a maximum specific surface area of 736.6 m2/g. Micropores were found to be contributing toward enhancing the specific surface area. AAC800 exhibited a maximum specific capacitance of 176.7 F/g at 0.5 A/g in 6.0 M KOH electrolyte in a three-electrode setup. A symmetric supercapacitor was fabricated using AAC800 as an active material in an organic electrolyte composed of 1.0 M tetraethylammonium tetrafluoroborate (TEABF4) as a conducting salt in the acetonitrile (ACN) solvent. The self-discharge of the cell/device was analyzed from fitting two different mathematical models; the cell also exhibited a remarkable coulombic efficiency of 100% over 10,000 charge/discharge cycles, retaining ∼93% capacitance at 2.3 V.